2019
DOI: 10.1016/j.toxrep.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of Cuphea ignea extract against benzo(a)pyrene-induced lung tumorigenesis in Swiss Albino mice

Abstract: HighlightsPhenolic compounds from Cuphea ignea extract were identified.Chemopreventive and chemotherapeutic potentials of C. ignea extract were demonstrated in mice.Tumor, inflammatory, oxidative stress, apoptotic and angiogenic markers were investigated.Histopathological analysis showed improved lung tissues after treatment with C. ignea extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…34 The significant drop in the relative lung weight and increased body weight by DAS were consistent with previous chemopreventive studies of various plant extracts and their active components in chemically induced lung cancer. [35][36][37] The histopathological data studies confirmed the tumor growth inhibitory and the protective effect of DAS in the lungs ( Figure 5A). The data also revealed that the pretreatment of DAS controlled the invasion of cancer cells in the liver leading to apoptosis ( Figure 5B).…”
Section: Dovepresssupporting
confidence: 53%
See 1 more Smart Citation
“…34 The significant drop in the relative lung weight and increased body weight by DAS were consistent with previous chemopreventive studies of various plant extracts and their active components in chemically induced lung cancer. [35][36][37] The histopathological data studies confirmed the tumor growth inhibitory and the protective effect of DAS in the lungs ( Figure 5A). The data also revealed that the pretreatment of DAS controlled the invasion of cancer cells in the liver leading to apoptosis ( Figure 5B).…”
Section: Dovepresssupporting
confidence: 53%
“…The results also agreed with the studies that reported the considerable decrease in the chemical carcinogen-induced activities of these tumor marker enzymes by different plant extracts or its active constituents. 36,47,48 A B Figure 9 Effect of DAS on the expression of FASN by IHC in lung and liver tissues. Notes: The representative images of IHC analysis of FASN expression in the: (A) lungs, (B) Liver.…”
Section: Dovepressmentioning
confidence: 99%
“…Cuphea ignea A. DC. Which is known as firecracker or cigar flower, is often grown as an ornamental plant in the tropics and as a summer bedding in the temperate zone [ 13 ]. Cuphea ignea A. DC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports revealed that Cuphea ignea A. DC. possesses significant antiulcerogenic, antitumor, antioxidant and antihypertensive activities [ [13] , [14] , [15] ]. Thirteen compounds were identified in Cuphea ignea A. DC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation